Exploring antifungal potential: The flavonoid composition of Machaerium villosum extracts against Cryptococcus neoformans (Research, Society and Development, 2024)
The escalating prevalence of fungal infections, coupled with the limitations and adverse effects associated with existing antifungal drugs, necessitates the exploration of alternative therapeutic approaches. The objective of this study was, therefore, to conduct a chemical analysis and assess the biological potential of the hydroethanolic extract obtained from the leaves of Machaerium villosum. Thus, this study investigates the extract from this plant, which belongs to the Fabaceae family, known for its rich flavonoid content. Employing UHPLC-ESI-IT-MS/MS, the extract was characterized, revealing the presence of various flavonoids, including glycosylated derivatives of kaempferol and quercetin, along with organic acids and fatty acid derivatives. The total flavonoid content was quantified at 45.7 mg/g. Subsequent antifungal evaluation unveiled significant activity against Cryptococcus neoformans, with a minimum inhibitory concentration (MIC) of 16 μg/ml and fungicidal action at 256 μg/ml. The observed efficacy against C. neoformans aligns with the documented antifungal properties of flavonoids, which disrupt membrane integrity and impede crucial cellular processes. The findings suggest that M. villosum extract, particularly its flavonoid constituents, holds promise as a potential source for developing new antifungal therapies.